Paulus se retoriese strategic in Galasiërs 2:11-21 - Tolmie, D. F. (Verbum et ecclesia, 2000)
Paul's rhetorical strategy in Galatians 2:11-21 The aim of this article is to demonstrate an approach to the rhetorical analysis of Paul's letter to the Galatians that differs from the typical approach followed by researchers, namely the forcing of ancient rhetorical categories on the letter. Instead, it is proposed that Paul's rhetorical strategy should be analysed in terms of a grounded theoretical approach. This is demonstrated by a systematic analysis of the Paul's basic rhetorical strategy, as well as of all the supportive persuasive techniques, in this pericope.